Status and Geographical Distribution of Indigenous and Quarantine Fruit Fly Species (Diptera: Tephritidae) in Sarawak - Fu, Felicia Kueh Tai; Gumbek, Megir; Hanapi, Sulaiman (Borneo Journal of Resource Science and Technology, 2016)
The provision of reliable pest records, one of which is fruit fly record, is one of the vital components under the International Plant Protection Convention. A fifteen-month survey to detect fruit flies using male pheromone lure trapping method was carried out from April 2010 to July 2011. The standard Steiner traps and three types of lures (ME-lure, CUE-lure and Trimed-lure) were used. The traps were placed at every five kilometre interval along the east-west trunk road of Sarawak. The geographical distribution of the fruit fly species was established through Global Positioning System mapping. Twenty species of Dacinae fruit flies which includes nine unknown Bactrocera species were detected along the east-west trunk road of Sarawak. The main species of fruit fly caught in the ME-lure trap were Bactrocera papayae, B. carambolae and B. umbrosa, whereas B. cucurbitae, B. papayae, B. caudata, B. tau, B. apicalis, B. nigrotibialis and B. albistrigata were caught in the CUE-lure trap. The quarantine species, which is species of potential economically importance in Sarawak, B. correcta, B. dorsalis, B. occipitalis and B. zonata were absent in both ME-lure and CUE-lure traps. The Mediterranean fruit fly (Ceratitis capitata) was not detected in the Trimed-lure trap. Out of the twelve identified species, eleven of them were detected along the main road of Sarawak. Bactrocera papayae and B. caudata were abundant, whereas the other species were more prevalent at some locations.